BldG and SCO3548 interact antagonistically to control key developmental processes in streptomyces coelicolor - Parashar, Archana; Bignell, Dawn R. D.; Leskiw, Brenda K.; Harcombe, Kimberley (My University, 2009)
The similarity of BldG and the downstream coexpressed protein SCO3548 to anti-anti-sigma and anti-sigma factors, respectively, together with the phenotype of a bldG mutant, suggests that BldG and SCO3548 interact as part of a regulatory system to control both antibiotic production and morphological differentiation in Streptomyces coelicolor. A combination of bacterial two-hybrid, affinity purification, and far-Western analyses demonstrated that there was self-interaction of both BldG and SCO3548, as well as a direct interaction between the two proteins. Furthermore, a genetic complementation experiment demonstrated that SCO3548 antagonizes the function of BldG, similar to other anti-anti-sigma/anti-sigma factor pairs. It is therefore proposed that BldG and SCO3548 form a partner-switching pair that regulates the function of one or more sigma factors in S. coelicolor. The conservation of bldG and sco3548 in other streptomycetes demonstrates that this system is likely a key regulatory switch controlling developmental processes throughout the genus Streptomyces.
Keywords: proteins; streptomyces coelicolor; genetics